The Role and Importance of Banks in the Development of Business Activity (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The role and importance of commercial banks in the sustainable development of industries and links of the economy, the financing of entrepreneurial activity are immeasurable. Based on this, this article discusses the issues of improving the activities of commercial banks.